ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9413548
|View full text |Cite
|
Sign up to set email alerts
|

Pause-Encoded Language Models for Recognition of Alzheimer’s Disease and Emotion

Abstract: We propose enhancing Transformer language models (BERT, RoBERTa) to take advantage of pauses. Pauses play an important role in speech. In previous work we developed a method to encode pauses in transcripts for recognition of Alzheimer's disease. In this study, we extend this idea to language models. We re-train BERT and RoBERTa using a large collection of pause-encoded transcripts, and conduct finetuning for two downstream tasks, recognition of Alzheimer's disease and emotion. Pause-encoded language models out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…WA ↑ UA ↑ MHA-3 [46] 74.0 75.3 F-III [47] 79.2 80.5 AugPauseRoBERTa [48] 72. This is because BERT encodes different properties for each layer.…”
Section: Methodsmentioning
confidence: 99%
“…WA ↑ UA ↑ MHA-3 [46] 74.0 75.3 F-III [47] 79.2 80.5 AugPauseRoBERTa [48] 72. This is because BERT encodes different properties for each layer.…”
Section: Methodsmentioning
confidence: 99%
“…16 Other reports based on language and speech features ranged from 70% to 89.6% accuracy. [17][18][19][20][21][22][23][24][25] While previous studies have shown promising results with speech features classifying the amnestic AD presentation versus HC, a clinically meaningful challenge that has not been addressed is distinguishing underlying ADNC from FTLD pathology in individuals presenting with non-amnestic phenotypes. In this study, we used digital speech features that were extracted with automatic lexical and acoustic pro- with different feature sets and applied an interpretable artificial intelligence (AI) approach to answer these questions.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study used a large dataset and a natural language processing (NLP) approach to differentiate individuals with dementia from HC with 87.1% accuracy and to distinguish individuals with mild cognitive impairment (MCI) from HC with 71.2% accuracy 16 . Other reports based on language and speech features ranged from 70% to 89.6% accuracy 17–25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation